Corneal Endothelial Morphology and Thickness Alterations in Patients With Severe Obstructive Sleep Apnea–Hypopnea Syndrome. Issue 1 (January 2021) - Chalkiadaki, Evangelia; Andreanos, Konstantinos; Florou, Chrysoula; Droutsas, Konstantinos; Maniou, Chrysoula; Amfilochiou, Anastasia; Georgalas, Ilias; Papaconstantinou, Dimitrios; Koutsandrea, Chrysanthi
Abstract : Purpose: To investigate central endothelial cell density (ECD), morphology, and central corneal thickness (CCT) in patients newly diagnosed with severe obstructive sleep apnea–hypopnea syndrome (OSAHS) and to determine the correlation between these parameters and OSAHS severity. Methods: This prospective, comparative case series was conducted in a university ophthalmology clinic. In total, 51 patients recently diagnosed with severe OSAHS (apnea–hypopnea index above 30) and a paired, age and sex-matched control group of 44 healthy individuals were enrolled. After detailed ophthalmologic examination, specular microscopy measurement was performed for all participants. Central ECD, average cell area, coefficient of variation (CV) of cell area, hexagonal cell appearance ratio (% Hex), and CCT were compared between the groups. The Pearson correlation test was also used to assess the influence of the polysomnographic findings, that is, the proportion of each stage of sleep, apnea–hypopnea index, SpO2, mean and maximum duration of apneas, oxygen desaturation index, and arousal index on corneal endothelial morphometric parameters and CCT. Results: A total of 190 eyes were examined: 102 eyes of patients with severe OSAHS and 88 eyes of the control group. The mean ECD, CV, % Hex, and CCT values in the OSAHS group were 2439.25 ± 344.36 cells/mm 2, 41.41 ± 11.62, 45.22 ± 7.06%, and 533.88 ± 40.53 μm, respectively. ECD and CCT did not significantly differ between the groups ( P = 0.46, P = 0.55, respectively). CV value was significantly higher ( P = 0.009), whereas the %Hex was significantly lower ( P = 0.01) in the OSAHS group. We observed a significant negative correlation between CCT and REM sleep percentage ( P = 0.005). Conclusions: Greater pleomorphism and polymegathism of corneal endothelium was found in patients with severe OSAHS when compared with healthy subjects. Low percentage of REM sleep, usually found in patients with OSAHS, may cause an increase in corneal thickness. Abstract : Supplemental Digital Content is Available in the Text.